From the middle stratosphere to the surface, using nitrous oxide to constrain the stratosphere–troposphere exchange of ozone - D. J. Ruiz; M. J. Prather (Atmospheric Chemistry and Physics, 2022)
Stratosphere–troposphere exchange (STE) is an important source of tropospheric ozone, affecting all of atmospheric chemistry, climate, and air quality. The study of impacts needs STE fluxes to be resolved by latitude and month, and for this, we rely on global chemistry models, whose results diverge greatly. Overall, we lack guidance from model–measurement metrics that inform us about processes and patterns related to the STE flux of ozone (O 3 ). In this work, we use modeled tracers (N 2 O and CFCl 3 ), whose distributions and budgets can be constrained by satellite and surface observations, allowing us to follow stratospheric signals across the tropopause. The satellite-derived photochemical loss of N 2 O on annual and quasi-biennial cycles can be matched by the models. The STE flux of N 2 O-depleted air in our chemistry transport model drives surface variability that closely matches observed fluctuations on both annual and quasi-biennial cycles, confirming the modeled flux. The observed tracer correlations between N 2 O and O 3 in the lowermost stratosphere provide a hemispheric scaling of the N 2 O STE flux to that of O 3 . For N 2 O and CFCl 3 , we model greater southern hemispheric STE fluxes, a result supported by some metrics, but counter to the prevailing theory of wave-driven stratospheric circulation. The STE flux of O 3 , however, is predominantly northern hemispheric, but evidence shows that this is caused by the Antarctic ozone hole reducing southern hemispheric O 3 STE by 14 %. Our best estimate of the current STE O 3 flux based on a range of constraints is 400 Tg(O 3 ) yr −1 , with a 1 σ uncertainty of ± 15 % and with a NH : SH ratio ranging from 50:50 to 60:40 . We identify a range of observational metrics that can better constrain the modeled STE O 3 flux in future assessments.